Review of the subgenus Euthraulus (Ephemeroptera, Leptophlebiidae, genus Choroterpes) from the Western Ghats (India) - Kluge, Nikita; Srinivasan, Pandiarajan; Vasanth, M.; Sivaruban, T.; Barathy, S.; Isack, Rajasekaran (Zootaxa, 2022)
The subgeneric name Monochoroterpes Kluge & Jacobus 2015 is regarded here to be a junior synonym of Euthraulus Barnard 1932 (syn. n.), based on a wider understanding of more species from each group. Based on male and female imagines reared from larvae, the following species are described or re-described: Choroterpes (Euthraulus) alagarensis Dinakaran et al. 2009, Ch. (E.) armillatus sp. n., Ch. (E.) latus sp. n., Ch. (E.) atelobranchis sp. n., Ch. (E.) unicolor sp. n., Ch. (E.) nambiyarensis Selva-Kumar et al. 2013, Ch. (E.) angustifolius sp. n. and Ch. (E.) nandini Selvakumar & Sivaramakrishnan 2015. All these species are distributed in southern India. One of them, Ch. (E.) latus sp. n., was collected in a plains river, Vaigai, in Madurai and in several localities in Sri Lanka, including a plains river, Malvatu, in Anuradhapura; formerly it was confused with another Ceylonese species, Ch. (E.) signatus (Hagen 1858). Here the characters separating Ch. (E.) signatus from Ch. (E.) latus sp. n. are reported and illustrated. Other species listed above were collected in mountain rivers in south of Western Ghats. One more species of Euthraulus is described without a formal name based a on mature male larva collected near Mumbai. The species description of Choroterpes (Euthraulus) kalladaensis Rekha et al. 2019 was based on specimens belonging both to Indialis rossi and Ch. (E.) angustifolius; since the type specimens are lost, and the description is based mainly on characters of Indialis rossi, we propose the following synonymy: Indialis rossi Peters 1975 = Choroterpes (Euthraulus) kalladaensis Rekha et al. 2019, syn. n.